2022
DOI: 10.1016/j.cmi.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of subgenomic RNA detection of viable SARS-CoV-2 in patients with COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…However, culture-based isolation is difficult, labor-intensive and time-consuming, and has suboptimal sensitivity for detecting viable viruses due to bacterial contamination or cell detachment. Accordingly, previous studies suggested that a subgenomic RNA assay may be useful for predicting the duration of infective viral shedding because this assay may be complementary to suboptimal sensitivity of cell culture for viable virus shedding [8][9][10][11]. Our previous study also found that, while subgenomic RNA was detected for a few days after the negative conversion of viral culture, the mean duration of viral shedding assessed by subgenomic RNA detection was notably similar to that of virus culture [11].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, culture-based isolation is difficult, labor-intensive and time-consuming, and has suboptimal sensitivity for detecting viable viruses due to bacterial contamination or cell detachment. Accordingly, previous studies suggested that a subgenomic RNA assay may be useful for predicting the duration of infective viral shedding because this assay may be complementary to suboptimal sensitivity of cell culture for viable virus shedding [8][9][10][11]. Our previous study also found that, while subgenomic RNA was detected for a few days after the negative conversion of viral culture, the mean duration of viral shedding assessed by subgenomic RNA detection was notably similar to that of virus culture [11].…”
Section: Discussionsupporting
confidence: 56%
“…Accordingly, previous studies suggested that a subgenomic RNA assay may be useful for predicting the duration of infective viral shedding because this assay may be complementary to suboptimal sensitivity of cell culture for viable virus shedding [8][9][10][11]. Our previous study also found that, while subgenomic RNA was detected for a few days after the negative conversion of viral culture, the mean duration of viral shedding assessed by subgenomic RNA detection was notably similar to that of virus culture [11]. Therefore, the true rate of viable SARS-CoV-2 shedding would lie between the sensitivity of cell culturepositive samples and that of subgenomic RNA-positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the detection of the RNA alone cannot demonstrate the viability of SARS- CoV-2, and the prolonged RNA shedding could be associated with non-infectious viral recovery, infectious virus from patients with extended RNA shedding has been previously reported in particular for immunocompromised ones [ 15 , 16 ]. Indeed, recent studies demonstrate that SARS-CoV-2 infection is associated with accelerated replication, high viral RNA titers and isolation of infectious virus during the acute phase, which is followed by a rapid decrease after the first two-three weeks [17] , [18] , [19] , [20] .…”
Section: Case Reportmentioning
confidence: 99%
“…sgRNAs are transcribed in infected cells and are poorly packaged into mature virions; thus, their presence could indicate the presence of active viral replication ( 13 ). Many studies demonstrated the correlation between sgRNA detection and isolation of viable virus ( 14 16 ), but some studies argued against the association ( 17 19 ). We aimed to study the kinetics of SARS-CoV-2 total RNAs and sgRNAs and their potential role as surrogate markers of viral infectivity.…”
Section: Introductionmentioning
confidence: 99%